(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
The study proposes the analysis of how the aesthetic elements articulated in the staging of Stabat Mater, by Janaina Leite, are related to the artist’s intention to propose a certain reordering of her family romance pieces, as well as a feminine one commonly related to the archetype of the Virgin Mother. The key to this enigma is situated on the female body, conjointly with the sacred and obscene, Leite presses on the reflections of this contradiction not only in his dramaturgy, but also in the visual aspects of his lecture-piece which, despite of searching for possible enigma meanings, it recognizes its impossible way to find meaning at its core, flawed, empty and, therefore, always prone to the construction of new meanings.